Psoriasis Vulgaris - Wizar Putri Mellaratna; Muhammad Naufal Arif (Jurnal Medika Nusantara, 2023)
Psoriasis is an inflammatory disease of the skin that is chronic, persistent, and repetitive due to complex abnormalities in epidermal growth and differentiation as well as multiple abnormalities of biochemical, immunological, and vascular properties. Generally, lesions in the form of erythematous plaques are layered with a silvery white color with firm borders. Its location can be localized, for example on the elbows, knees or scalp or affect almost 100% of the body area. The prevalence of psoriasis varies from 1 to 12% among different populations worldwide with a male to female ratio of 1:1. The cause of psoriasis until now is still unclear and what is already known are the factors that influence the onset of psoriasis based on epidemiological data, including nation, region, climate, heredity, and other factors.